AISAS-Based Content Writing Strategies to Increase Instagram Engagement: A Case Study of News Accounts @Tvonenews - Sophie Sita Amalia; Ressa Uli Patrissia (Journal of Social Research, 2025)
The rapid growth of digital media has transformed how news is consumed, with Instagram emerging as a key platform for information dissemination. However, many news accounts, including @tvonenews, struggle with low audience engagement due to ineffective content strategies. This study examines how AISAS (Attention, Interest, Search, Action, Share)-based content writing strategies can enhance engagement on Instagram news accounts. This study aims to analyze the content writing strategy on the Instagram account @tvonenews in increasing audience engagement through the AISAS (Attention, Interest, Search, Action, Share) model approach. The method used is qualitative descriptive, employing observation techniques, literature studies, and interviews. The results show that the use of catchy headlines, informative and persuasive captions, and the integration of call-to-action (CTA) and relevant hashtags significantly increases engagement rates. Content that has been intervened shows an increase in the number of likes, comments, shares, and saves compared to before. The application of the AISAS model has proven effective in shaping two-way engagement with audiences and strengthening media imagery in the digital age. This research provides practical contributions for media institutions in designing content that is more communicative and responsive to information consumption behavior on social media.